School Choice in China: Past, Present, and Future. (March 2019) - Dong, Hui; Li, Lulu
Purpose: Focusing on the hot-debating issue of school choice in China, this article aims to present a narrative of the policy interventions, especially promulgated by the Chinese central government during the past 20 years, and to discuss those challenges facing the governments and the society as a whole in the new era. Design/Approach/Methods: This article conceptually approaches the topic based on policy texts analysis and literature review. Findings: This article pictures the historical dynamics of school choice phenomenon and its interaction with the corresponding policy initiatives promoted by the central government. It argues that school choice governing in China basically experienced three stages since the middle of 1990s, namely controlling "choice fees, " promoting equalization and equity as well as comprehensive governance toward greater quality and equity. The effective implementation of these policy measures is gradually cooling down the "choice fever" in urban areas and restoring order for student enrollment in compulsory education, but great challenges are still lying ahead since the problem of school choice turns to be "wicked" in nature and cannot be simply solved within the education sector. Originality/Value: This article contributes to the global discourse of school choice research with much updated information of policy initiatives and the newly emerged situations since 2014, calling for close attention and deeper research from researchers both from China and from abroad.